Tax Policy Restores the Economy After a Disaster: A Comparative Perspective of Indonesia, the Philippines, and the United States - Kaca Dian Meila; Astari Dianty (JASF: Journal of Accounting and Strategic Finance, 2026)
Purpose: This study aims to compare the design, implementation mechanisms, and policy objectives of post-disaster tax incentives in Indonesia, the Philippines, and the United States, while examining how differences in fiscal capacity, institutional arrangements, and tax administration systems influence their effectiveness in supporting economic recovery. Method: This study employs a comparative qualitative approach based on a systematic literature review and document analysis. The literature selection process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. Data were collected from academic publications, government regulations, policy reports, and official documents published between 2010 and 2026. The selected studies were analysed using directed qualitative content analysis across five comparative dimensions: types of tax incentives, administrative tax relief, target beneficiaries, institutional arrangements, and contributions to economic recovery. Findings: The findings indicate that Indonesia, the Philippines, and the United States all utilize tax policy as a fiscal instrument to support post-disaster economic recovery through tax relief, filing and payment extensions, and administrative assistance. However, significant differences exist in policy design and implementation. Indonesia adopts a centralized approach, the Philippines combines central and local government coordination, while the United States operates through a comprehensive federal framework with broader tax benefits and stronger institutional capacity. The effectiveness of post-disaster tax incentives is influenced not only by fiscal resources but also by administrative efficiency, legal frameworks, and institutional coordination. Implications: The findings suggest that governments should strengthen interagency coordination, improve tax administration systems, and integrate tax incentives into broader disaster risk financing and recovery strategies to enhance policy effectiveness. Novelty/Value: This study contributes to the growing literature on disaster-responsive fiscal policy by providing a comparative analysis of post-disaster tax incentives in both developing and developed countries. The study offers a more comprehensive understanding of how fiscal capacity, institutional governance, and tax administration systems influence the effectiveness of tax incentives, while also providing policy lessons for the design of more responsive, equitable, and resilient tax policies in the face of natural disasters.